33 NHSBT tissue and eye services clinical support nurse team: advanced nursing practice. (16th November 2022) - Winstanley, Emma; Chandrasekar, Akila; Carroll, Vicki; Ambrose, Anita; Brown, Mark; Lyon, Marc; Paulus, Ulrike; Wells, Angus
Abstract : NHS Blood and Transplant (NHSBT) Tissue and Eye Services (TES) save and improve the lives of thousands of patients every year. The Clinical Support Nurse Team (CSNT) within TES is an example of registered nurses working at an advanced level, making professionally autonomous decisions for which they are accountable. The concept of nurses working at this level began with a pilot study in 2012 under a robust governance system and change process within NHSBT. The development and progress of the team has also been reviewed by NHSBT Clinical Audit. The CSNT currently comprises two band 7 nurses and a band 8a manager who work together to safely assess and authorise donated tissue for transplant. There are plans to expand the team in 2022 and to ensure that the work is underpinned by a suitable academic framework that reflects the level of clinical responsibility. The CSNT work in conjunction with TES medical consultants who provide education, guidance and governance. The team is required to use complex reasoning, critical thinking, reflection and analysis to inform their assessment and clinical judgement. CSNT practice is guided by the Donor Selection Guidelines set by the Joint United Kingdom (UK) Blood Transfusion and Tissue Transplantation Services Professional Advisory Committee (2013). These guidelines stipulate contraindications to tissue donation on which the CSNT bases clinical decisions to ensure the safety of the recipients of any donated tissue by ruling out the chances of contracting any transmissible illness or transplanting tissue of compromised quality. Although a large component of the TES CSNT workload is to authorise donor files from deceased donors there are also living donation programmes. CSNT also review the Autologous/Allogeneic Serum Eye Drop Programme (ASE/AlloSE). This involves reviewing clinical requests made by ophthalmologists for serum eye drop options. This is a brief summary of how CSNT nurses apply their expert knowledge and skills to a broad range of Clinically challenging and complex situations.